2013
DOI: 10.1038/hr.2012.224
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone is synthesized in and activates bulbospinal neurons through mineralocorticoid receptors and ENaCs in the RVLM

Abstract: The effects of aldosterone and mineralocorticoid receptor (MR) blockers on presympathetic neurons in the rostral ventrolateral medulla (RVLM) are well studied. To directly investigate whether aldosterone, eplerenone (an MR blocker), FAD286 (an aldosterone synthase inhibitor) and benzamil (an epithelial sodium channel (ENaC) blocker) affect RVLM neurons, we examined changes in the membrane potentials (MPs) of bulbospinal RVLM neurons using the whole-cell patch-clamp technique during superfusion with these drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…29 Aldosterone has been shown to exert its effects through genomic or non-genomic pathway. 30 Genomic effects of aldosterone are generally thought to be mediated by the MR and involve transcription, while aldosterone can also exert rapid nongenomic effects that are not blocked by inhibitors of transcription. 31 Numerous cell culture, animal, and human studies have shown aldosterone and the MR are implicated in activation of a variety of pathologic processes including inflammation, remodelling, and fibrosis in several target organs.…”
Section: Discussionmentioning
confidence: 99%
“…29 Aldosterone has been shown to exert its effects through genomic or non-genomic pathway. 30 Genomic effects of aldosterone are generally thought to be mediated by the MR and involve transcription, while aldosterone can also exert rapid nongenomic effects that are not blocked by inhibitors of transcription. 31 Numerous cell culture, animal, and human studies have shown aldosterone and the MR are implicated in activation of a variety of pathologic processes including inflammation, remodelling, and fibrosis in several target organs.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid recording respiratory neuronal activities, we examined the phrenic nerve activity from the ventral root of C 4 and excluded neurons that displayed a strong phasic relationship with phrenic nerve discharges from the subsequent experiments. 17,18,22 …”
Section: Experimental Procedures General Preparationsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] The experimental protocols were approved by the Institutional Review Board of National Defense Medical College in accordance with the National Guidelines for the Conduct of Animal Experiments. Briefly, with the animals under deep ether anesthesia, the brainstem-spinal cord was isolated at the T helper type 2 (Th 2 ) level, and the brainstem was sectioned between the roots of cranial nerve VI and the lower border of the trapezoid body.…”
Section: Experimental Procedures General Preparationsmentioning
confidence: 99%
See 2 more Smart Citations